The paperboy - Pilkey, Dav 1966- (New York Orchard Books, 1999)
A paperboy and his dog enjoy the quiet of the early morning as they go about their rounds.
1st Orchard pbk. ed.
A Caldecott Honor Book
Keywords: Newspaper carriers -- Fiction; Morning -- Fiction